The objective of the Lisbon Strategy to debate: study of the evolution of the use of ICT Leon and Palencia (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
The Lisbon Strategy intended to situate Europe way ahead in the subject of the Society Information and Knowledge. The member States have doubled their effortsever since, so that companies and citizens have a higher access to knowledge through the utilization of technology. The purpose of this article is to identify a descriptive and conglomerate analysis of the mining districts of Leon and Palencia, Spain, in respect to the utilization of ICTs, in accordance to what has been outlined in the Lisbon Strategy. The results obtained allowed us to determine if there has been a positive evolution in the incorporation of technology in the citizens’ and regional companies’ everyday’s life.
Keywords: ICT; León and Palencia; Multidimensional Analysis.